Empowering Youth who Care About Democracy: Introducing General Elections to First-Time Voters - Adwin Adofo (Journal of Universal Community Empowerment Provision, 2022)
The goal of this initiative was to educate first-time voters about the democratic process and give young people a voice in civic life. Workshops were held to teach people how to vote, drives were organized to get people registered to vote, there was a social media campaign, and there was even an attempt to get people out to the polls on election day. The initiative's stated purpose was to help first-time voters become actively engaged in the political process by increasing their turnout at the polls. Participants' increased knowledge and confidence in their abilities to vote in the main election indicates that the program achieved its purpose. Participants gained a grasp of the democratic process, candidates, and problems through the seminars, and all eligible citizens were registered to vote through the voter registration efforts. Election day mobilization provided participants with resources and support to ensure they were able to cast ballots, while the social media campaign helped to engage people and establish a feeling of community. In general, the program achieved its goal of encouraging first-time voters to cast ballots. This program's success exemplifies the power of young people to determine the future of their communities and countries via education and engagement, and it demonstrates the relevance of these factors in building a healthy and vibrant democracy.